Exploration of first-time fathers' experiences during the child's first year - Thilagavathy Ganapathy (Wolters Kluwer Medknow Publications, 2016)
Background: The paternal postpartum period is a tremendous transitional time for first-time fathers and so, their unique experiences should be considered. Aim: To explore new fathers' experiences during the child's first year and the factors associated with their experiences. Setting and Design: A descriptive exploratory research conducted among n = 149 new fathers working in private companies in Bengaluru, Karnataka, India recruited by purposive sampling during their first year of paternal postpartum period. Materials and Methods: An individual interview using a four-point structured rating scale consisting of 50 items measuring their experiences during the first year of paternal postpartum period was used to collect data. Statistical Analysis: All statistical analyses were performed by the Statistical Package for the Social Sciences (SPSS) 17 version. An alpha less than 0.05 was considered to be significant in all analyses. Results: The results revealed that the vast majority of the first-time fathers (61.34%) had positive postpartum experiences as compared to 38.66% who reported negative fatherhood experiences. The key concepts related to their experiences were emotional upheaval, changes in lifestyle, pleasant and rejuvenating fatherhood experiences, relationship difficulties with partners, parents, friends, lack of intimacy with spouse, feelings of social isolation, lack of leisure activities and hobbies, difficulties in balancing career and family, ongoing physical problems, and financial constraints. There was no association of their postpartum paternal experiences with sociodemographic factors. Conclusion: Findings from this study suggest the need for realigning health services that have traditionally focused on mothers and children to father friendly services that respect fathers' strengths, experiences, knowledge, relationship, empowerment, and well-being to promote lasting benefits for fathers and their families.